Robert B. Parker's The bitterest pill [large type] - Coleman, Reed Farrel, 1956- (Parker, Robert B., 1932-2010. Jesse Stone novels, 2019)
When a high school cheerleader dies of a suspected heroin overdose, it's clear that the opioid epidemic has reached the idyllic town of Paradise. Police chief Jesse Stone must unravel the supply chain and unmask the criminals behind it. The investigation's epicenter is Paradise High School, a prime market for Boston dealers looking to expand into the suburbs. As he digs deeper into the case, Jesse must battle self-interested administrators, reluctant teachers, distrustful teens, and overprotective parents. But the true bad guys are the ones with a lucrative business they'd kill to protect.